Strategi Komunikasi Divisi General Affair PT The UNV Serang dalam Mengelola Hubungan Kerja dengan Tenaga Outsourcing - Ahmad Firmansyah; Achmad Nashrudin Priatna; Noerma Kurnia Fajarwati; April Laksana; Putri Handayani (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to describe and analyze the communication strategy of the General Affairs (GA) Division of PT The UNV Serang in managing work relationships with outsourced workers from PT Tri Karya Cemerlang (TKC). Using a qualitative approach and in-depth interview methods, this study found that the GA Division implemented a structured and effective communication strategy, reflecting a deep understanding of Communication Strategy Theory, Organizational Communication, and Communication Management. The strategy involved thorough planning, flexible implementation, and continuous evaluation. The GA Division used various communication channels such as WhatsApp groups, weekly face-to-face meetings, and the use of visual media (photos/videos) to ensure clear and directed communication. This multi-channel approach facilitated timely and accurate information flow between departments and outsourced workers. Additionally, the GA Division positioned itself as a